2015
DOI: 10.1158/1538-8514.tumang15-b27
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B27: Activin A induces vascular endothelial cell proliferation and angiogenesis in oral cancer

Abstract: Solid tumors must develop direct and indirect ways to induce angiogenesis in order to continue progression and expansion. The expression of angiogenic factors in the tumor microenvironment is a complex process involving interactions among different cell types. Previous studies demonstrated activin A, a member of the TGF-β superfamily, participates in the development and progression of oral squamous cell carcinomas (OSCC) via regulation of the tumor microenvironment, but its effects in the modulation of angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the role of Activin A in angiogenesis is controversial [36]. While it was demonstrated to inhibit the cellular growth of vascular endothelial cells [37][38][39], contrasting findings showed that Activin A induced vascular endothelial cells proliferation [40]. Supporting this observation, Activin A was also found to induce VEGF expression leading to recruitment of blood vessels in vitro [41].This discrepancy of the pro-and anti-angiogenic role of activin A can be explained by the dual role of TGF-β [39]which share the Smad intracellular signalling proteins with TGF-β [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of Activin A in angiogenesis is controversial [36]. While it was demonstrated to inhibit the cellular growth of vascular endothelial cells [37][38][39], contrasting findings showed that Activin A induced vascular endothelial cells proliferation [40]. Supporting this observation, Activin A was also found to induce VEGF expression leading to recruitment of blood vessels in vitro [41].This discrepancy of the pro-and anti-angiogenic role of activin A can be explained by the dual role of TGF-β [39]which share the Smad intracellular signalling proteins with TGF-β [42].…”
Section: Discussionmentioning
confidence: 99%